2010
DOI: 10.2478/s11532-010-0012-4
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative and quantitative analysis of gallic acid in Alchemilla vulgaris, Allium ursinum, Acorus calamus and Solidago virga-aurea by chip-electrospray ionization mass spectrometry and high performance liquid chromatography

Abstract: This study presents the results obtained from qualitative and quantitative analysis of gallic acid from hydro-alcoholic extracts (methanol, ethanol) of plants from Plantae regnum. Plant qualitative analysis was performed using a novel mass spectrometric (MS) method based on fully automated chip-nanoelectrospray ionization (nanoESI) high capacity ion trap (HCT) while quantitative analysis was carried out by high performance liquid chromatography (HPLC). These methods were applied to Alchemilla vulgaris -common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Leaves mainly are the waist product of this plant. Few published paper suggested that leaves have the same, and even richer than the cloves content of sulphur compounds (allicin), chlorophylls, carotenoids, phenolic compounds, and vitamin C [2,8,32].…”
Section: Introductionmentioning
confidence: 99%
“…Leaves mainly are the waist product of this plant. Few published paper suggested that leaves have the same, and even richer than the cloves content of sulphur compounds (allicin), chlorophylls, carotenoids, phenolic compounds, and vitamin C [2,8,32].…”
Section: Introductionmentioning
confidence: 99%
“…The liquid extracts of A. vulgaris were previously shown to contain flavonoid glycosides composed of quercetin derivatives[ 3 ] and gallic acid. [ 4 ] Supportively, in our recent study, we also determined that the flavonoid amount of A. vulgaris is much higher in the methanol than the aqueous extract and as analysed by HPLC-DAD both extracts contained quercetin and gallic acid as the major vasoactive constituents. [ 10 ] Of these constituents, quercetin was demonstrated to induce relaxations[ 11 ] whereas; gallic acid was reported to produce contractions in isolated rat aorta.…”
Section: Discussionmentioning
confidence: 65%
“…Alchemilla vulgaris ( A. vulgaris ; lady's mantle), a member of the Rosaceaea family, has traditionally been used to treat bleeding, eczema, inflammation, diarrhoea, ulcers, skin rashes, menstruation disorders and oedema in Europe. [ 3 4 ] It is also used as herbal tea for hypertension[ 5 6 ] and as infusion for diabetes. [ 7 ] Liquid extracts of A. vulgaris were shown to contain flavonoid glycosides composed of quercetin derivatives[ 3 ] and gallic acid.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species of genus Alchemilla have been studied mainly for the content of flavonoids, triterpenes, tannins and total phenols [3][4][5][6] . With regard to phenolic acids, we only had data for the content of ellagic and gallic acids in Alchemilla species 7,8 . Phenolic compounds are considered free-radical scavengers 9,10 .…”
mentioning
confidence: 99%